Photovoltaic DG with accumulation, active and reactive power control for grid-connected and intentional islanding operations - Alves, Marcos G. [UNESP]; Melo, Guilherme A. [UNESP]; Canesin, Carlos A. [UNESP]; De Brito, Moacyr A.G. (Institute of Electrical and Electronics Engineers (IEEE), 2017)
Considering the new challenges in the energetic scenario around the world, this paper proposes the implementation of a micro-grid with photovoltaic generation and local accumulation, considering its capability to operate connected or islanded from the utility grid. The system will supply power to utility grid and local loads through six single-phase inverters in wye configuration, three of them operating in islanded or grid-Tie mode and other three inverters operating only in grid-Tie mode. Supporting the stability and power quality for the utility grid, lead-Acid batteries afford the backup energy allowing the electric power supply for the utility in absence of photovoltaic generation. While most inverters for distributed generation (DG) are designed to provide active power and to operate with a fixed power factor, in this paper the inverters are used to dynamically control the active and reactive power supply. Consequently, the system is able to perform as an active compensator at the point of common coupling, improving the power quality.
Keywords: Bidirectional power flow; Energy management; Micro-grid; Photovoltaic systems; Reactive power control; Smart grids